2013
DOI: 10.1093/ejo/cjt051
|View full text |Cite
|
Sign up to set email alerts
|

Bonding orthodontics brackets to enamel using experimental composites with an iodonium salt

Abstract: The use of a ternary photoactivation system containing an iodonium salt in bonding composites may allow bonding brackets to enamel using reduced light exposure times.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
7
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 19 publications
4
7
0
Order By: Relevance
“…Generally, an increased SBS was observed when DPIHFP-modified agents were incorporated in experimental composites for all light-activation times. This finding is in agreement with a previous study with experimental composites, which also found significantly higher SBS in relation to the control group, but using diphenyliodonium chloride (DPC) as iodonium salt (9). The higher bond strength of experimental composites using DPIHFP-modified agents may be explained by the fact that the salt, even in low concentration, can promote higher polymerization reactivity.…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…Generally, an increased SBS was observed when DPIHFP-modified agents were incorporated in experimental composites for all light-activation times. This finding is in agreement with a previous study with experimental composites, which also found significantly higher SBS in relation to the control group, but using diphenyliodonium chloride (DPC) as iodonium salt (9). The higher bond strength of experimental composites using DPIHFP-modified agents may be explained by the fact that the salt, even in low concentration, can promote higher polymerization reactivity.…”
Section: Discussionsupporting
confidence: 92%
“…This study is a follow up of the investigations on the use of iodonium salts to improve the polymerization of resin-based dental cements (9,19). The three experimental materials tested were obtained using diphenyliodonium hexafluorphosphate (DPIHFP; Sigma-Aldrich, Milwaukee, WI, USA) at molar concentrations of 0 (control), 0.5, or 1%.…”
Section: Experimental Compositesmentioning
confidence: 99%
See 3 more Smart Citations